Genesis (Northbrook, Ill. Roland Collection, 1993)
Examines the making of works of art by the poet Ida Gerhardt, the painter Armando, the choreographer Hans Van Manen, the composer Reinbert de Leeuw and the sculptor Carel Visser.
VHS format.
Director / scenario, Cherry Duyns.